Brain network dynamics during working memory are modulated by dopamine and diminished in schizophrenia - Urs Braun; Anais Harneit; Giulio Pergola; Tommaso Menara; Axel Schäfer; Richard F. Betzel; Zhenxiang Zang; Janina I. Schweiger; Xiaolong Zhang; Kristina Schwarz; Junfang Chen; Giuseppe Blasi; et al. (Nature Communications, 2021)
Working memory requires the brain to switch between cognitive states and activity patterns. Here, the authors show that the steering of these neural network dynamics is influenced by dopamine D1- and D2-receptor function and altered in schizophrenia.